CHARACTER EDUCATION VALUES REPRESENTATION IN SENIOR HIGH SCHOOL ENGLISH TEXTBOOK: CRITICAL DISCOURSE ANALYSIS - Galih Rayi Pradana (PROJECT (Professional Journal of English Education), 2023)
This study purposes to analyze the moral values contained in English Textbook for Tenth Grade. The author uses the Critical Discourse Analysis research method from Halliday (1978). The explanation expressed by Richards (2001) that having a good component that is conveyed through textbooks is an essential point that can influence readers. The books analyzed by the author are English textbooks from Widiati et al. (2017). The author displays each chapter along with the page according to the character education moral values displayed in the English textbook. The findings that the author has researched are giving very good results by providing information, giving a sense of respect for one another, and having religious values that educators and students must apply in daily life. It is necessary to have a combination of educators with students for English textbooks in or outside the school environment. The points of the book which have been analyzed by the author are suitable for use because they have important roles and follow MONEC. Keywords:  Moral Value; Education; Critical Discourse Analysis